Sex Estimation On Thoracic Vertebrae: A Systematic Review - Rani Sakaran; Aspalilah Binti Alias; Choy Ker Woon; Nurul Hannim Zaidun; Nur Damia Iwani Zulkiflee; Ng Wei Lin; Eric Chung; Ku Mastura Ku Mohd Noor (ELSEVIER, 2024)
Indexed by Scopus